A prospective case series in regenerative endodontics: The effective use of diluted antibiotic hydrogels in endodontic regeneration procedures - Alaa H.A Sabrah; Mohammad M. Hammad; Fouad K Wahab; Abeer AlHadidi; Nesreen A Salim; Ayman F. Alelaimat; Ibrahim Khatib (Elsevier, 2023)
Objective: to investigate the effectiveness of diluted antibiotic hydrogels in endodontic regeneration procedures. Materials and Methods: One conventional treatment (calcium hydroxide) and two experimental treatments containing 1 mg/mL antibiotic in gel (MC-TAP and MC-DAP) were prepared for this study. The effect of these medicaments on the proliferation and differentiation potential of dental pulp stem cells (DPSCs) was examined before their clinical use, using WST and ALP assays. Twenty-two teeth diagnosed with necrotic immature roots were treated with calcium hydroxide, MC-TAP or MC-DAP using the endodontic regeneration protocol as described by the American Association of Endodontists (AAE). Teeth were examined after application of the medicament, at the time of regeneration and after 12-24 months. Results: All treated teeth showed resolution of signs and symptoms shortly after treatment with the different medicaments. However, signs and symptoms returned a few months after initial treatment in clinical cases treated with MC-DAP. All successfully treated teeth examined after 12-24 months were free of signs and symptoms, but vitality was not achieved. Conclusion: Low concentration antibiotic gel containing triple antibiotic paste (MC-TAP) can be successfully used for endodontic regeneration procedures.